Analisis Kebijakan Rehabilitasi pada Orang dengan Ganguan Jiwa di Yayasan Indocharis - Nadlifuddin, Mohammad Ilham; Azizah, Ummi Nasryatul; Nurfatika, Lingga Ayu Salma; Hikmah, Bintan Wahdatul; Yanti, Dewi (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
This study aims to analyze the implementation of rehabilitation policies for people with mental disorders (ODGJ) at the Indocharis Foundation. Through in-depth interviews and non-participant observation, this study analyzes to what extent national policies are reflected in the rehabilitation practices carried out by the foundation. The results of the study show that the Indocharis Foundation has implemented various comprehensive rehabilitation programs, including medical therapy, non-medical therapy, vocational training, and social integration support. These programs are in line with the mandate of the Republic of Indonesia Minister of Health Regulation Number 54 of 2017. In addition, the foundation is also active in efforts to reduce stigma through socialization and education to the community. However, there are still several areas that need to be improved, such as expanding cooperation with companies to open up job opportunities for clients, and increasing the intensity of home visits to monitor clients' conditions on an ongoing basis. This study concludes that the rehabilitation policy at the Indocharis Foundation has been running well, but there needs to be continuous efforts to improve the quality of services and expand the scope of the program.